Analisis Lingkungan Bisnis dalam Ekonomi Digital: Mengukur Dampak Platformisasi Terhadap Persaingan Industri - Zuhrinal M. Nawawi; Julia Hamdini Nasution (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study uses a qualitative method to analyze the dynamics of the business environment within the context of the digital economy, specifically focusing on the impact of platformization on industry competition. Rapid digital technological developments have given rise to various digital platforms that disrupt conventional business models and reshape market structures across multiple sectors. Platforms such as marketplaces, ride-sharing services, and fintech companies have become dominant actors influencing competitive patterns, value distribution, and relationships between large and small enterprises. This research aims to understand how digital platforms affect industry competition through vertical integration, network effects, and data control. The findings reveal that platformization enhances transaction efficiency and market access but also creates imbalances in market power, digital monopolies, and dependency on algorithms. In this context, government regulation and business adaptation strategies are essential to maintaining competitive balance and ensuring the sustainability of the digital ecosystem. The study recommends the adoption of adaptive regulatory approaches and multi-sector collaboration to foster healthy competition in the digital era.